(untitled) (Polis (Santiago), 2018)
This essay argues that the iron epistemic circularity of economic science makes non-viable to found a different way of understanding the natural world economically from the criticism of its theoretical foundations nor if its practice. The theoretical challenge, he notes, is to illuminate another world that can build another economic problem, and another way of understanding the solution to this economic problem that, ultimately, generate less sense of futility than generated by the current economic theory. The author proposes a systemic ontology as the foundation of an ecosystemic economy optimization, while claiming no solution of continuity between endosystemic and ecosystemic , and posits that we must move from a close system to an open one.